2020
DOI: 10.1177/1354816620921298
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of economic policy uncertainty on the relationship between tourism and economic growth with an MF-VAR model

Abstract: Using a mixed-frequency vector autoregressive (MF-VAR) model, this article attempts to determine whether or not the relationship between tourism and economic growth changes in the presence or absence of economic policy uncertainty (EPU) shock. Moreover, we further our analysis by focusing on whether or not there is a significant difference in the distinct impact intensity of Hong Kong, Chinese, and global EPU. The study period spans April 1998 to March 2018. The results indicate the following. First, the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 87 publications
1
21
0
2
Order By: Relevance
“…In the standard VAR modelling, the potential drivers identified by the literature are the real effective ER (Kuo, Wang, Hwang, & Ye, 2009;Nowjee, Poloodoo, Lamport, Padachi, & Ramdhony, 2012;Webber, 2001), real personal disposable income per capita (Lee, Fu, & Peng, 2015), the geopolitical risk index (GPR) (Antonakakis, Gupta, Kollias, & Papadamou, 2017;Bassil, Saleh, & Anwar, 2019;Lanouar & Goaied, 2019), the US economic policy uncertainty (Balli, Uddin, & Shahzad, 2019;Gozgor & Ongan, 2017;Sharma, 2019) and global economic policy uncertainty (Akadiri, Alola, & Uzuner, 2019;Liu, Liu, & Wang, 2020;Nguyen, Schinckus, & Su, 2020;Wu & Wu, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In the standard VAR modelling, the potential drivers identified by the literature are the real effective ER (Kuo, Wang, Hwang, & Ye, 2009;Nowjee, Poloodoo, Lamport, Padachi, & Ramdhony, 2012;Webber, 2001), real personal disposable income per capita (Lee, Fu, & Peng, 2015), the geopolitical risk index (GPR) (Antonakakis, Gupta, Kollias, & Papadamou, 2017;Bassil, Saleh, & Anwar, 2019;Lanouar & Goaied, 2019), the US economic policy uncertainty (Balli, Uddin, & Shahzad, 2019;Gozgor & Ongan, 2017;Sharma, 2019) and global economic policy uncertainty (Akadiri, Alola, & Uzuner, 2019;Liu, Liu, & Wang, 2020;Nguyen, Schinckus, & Su, 2020;Wu & Wu, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In that way, environmental policies induce environmental quality. Similarly, Liu et al (2020) attempted to evaluate the impact of EPU on the tourism-growth nexus. Using the case study of Hong Kong, Chinese, and global EPU, the authors suggested that EPU influences the size of the impulse response.…”
Section: Economic Policy Uncertainty and Environment Nexusmentioning
confidence: 99%
“…When governments regard traditional local characteristics of products and gourmet tourism as the focus of development, they play a decisive role in revitalizing traditional cuisine (Ang, 2018; Haque and Thaku, 2015; Shinohara, 2017, Liu et al , 2021). Since the adoption of tourism policies depends on economic conditions, the dissemination of such policies will increase as the appeal of traditional cuisine to international tourists increases over time.…”
Section: Literature Reviewmentioning
confidence: 99%